2012
DOI: 10.1590/s1517-97022012000300011
|View full text |Cite
|
Sign up to set email alerts
|

Regulação educativa e trabalho docente em Minas Gerais: a obrigação de resultados

Abstract: Este artigo apresenta a descrição e a análise das políticas educacionais em desenvolvimento no sistema estadual de ensino em Minas Gerais, tendo por objetivo identificar seus efeitos sobre as relações de trabalho docente. Tais políticas educacionais enquadram-se na modalidade de regulação educativa denominada obrigação de resultados, que compreende um conjunto de intervenções caracterizadas como medidas de controle com o propósito de obter maior eficácia escolar. O levantamento documental e a análise dos dados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 2 publications
0
4
0
10
Order By: Relevance
“…In phases (1) and (2), through the use of the Eric and Scielo databases, I procured and selected articles related to school production, school results, school evaluation performance and school knowledge (Augusto, 2012;Bergamo and Bernardes, 2006;de Miranda Barbosa and Vieira, 2013;Erazo, 2013;Mesquita, 2012;Milner, 2013;Nonay, 2014;Trindade and Prigenzi, 2002). Official documents of the colombian national government on evaluation (ICFES, 2015) have been also studied, which is the reality closest to the research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In phases (1) and (2), through the use of the Eric and Scielo databases, I procured and selected articles related to school production, school results, school evaluation performance and school knowledge (Augusto, 2012;Bergamo and Bernardes, 2006;de Miranda Barbosa and Vieira, 2013;Erazo, 2013;Mesquita, 2012;Milner, 2013;Nonay, 2014;Trindade and Prigenzi, 2002). Official documents of the colombian national government on evaluation (ICFES, 2015) have been also studied, which is the reality closest to the research.…”
Section: Methodsmentioning
confidence: 99%
“…In the same sense, school results have consequences on teaching work. Augusto (2012) showed that there are teacher work definition categories, such as: good, responsible, high performance, competent, regular, insufficient, excellent and excluded by low performance (OECD, 2010). This, without ignoring, the possible organizational forms induced within the school in attention to professional compliance: teaching staff distribution in levels and teaching areas according to the capacity or performance expectations.…”
Section: School Knowledge Distribution and Productionmentioning
confidence: 99%
“…Este artigo, que é fruto de uma dissertação de mestrado, assume relevância acadêmica pelo fato de haver indícios, por meio de levantamento bibliográfico realizado (AUGUSTO, 2010(AUGUSTO, , 2011(AUGUSTO, , 2012BARBOSA, 2013 intensificação e precarização do trabalho docente (OLIVEIRA E VIEIRA, 2012;OLIVEIRA, 2007;DUARTE, 2013).…”
Section: Metodologia E Justificativaunclassified
“…As políticas de gerenciamento dos professores introduzem sistemas racionalistas nas práticas de ensino, incitando a competição e o individualismo, e induzindo à precarização do trabalho dos professores, a um mal-estar docente e aum clima organizacional tenso, enfadonho e desumano (Rodriguez, 2008;Assunção & Oliveira, 2009;Calderón, 2009;Garcia, 2009;Nogueira, 2011;Augusto, 2012;Lelis, 2012).…”
Section: Novas Estratégias Gerenciais E Novas Atitudes Docentes: a Caunclassified